The well-being of santri in relation to self-adjustment and parents’ occupations - Wardani, Alfi Rilya Ulvia; Hertinjung, Wisnu Sri (Program Studi bimbingan Konseling PPs UNM Makassar, 2024)
Research has found that santri have poor well-being, hindering their ability to optimize their potential at pesantren. Santri often experience discomfort and pressure due to significant differences in routines and facilities between home and pesantren. This study aims to investigate santri’s well-being in relation to their self-adjustment and their parents’ occupations. This study was conducted using a quantitative correlational method. Data on well-being and self-adjustment were collected using the Indonesian Santri Well-Being Scale and the Psychological Adjustment Scale (PAS). Data on parents’ occupations were gathered through the biodata section of the questionnaire sheet. Selected using purposive cluster random sampling, the study included 175 santri from the tenth and eleventh grades at Pesantren X, aged between 15 and 18 years. Data were analyzed using the ANCOVA test. The results revealed a positive correlation between self-adjustment and santri’s well-being, with a contribution of 26.6% (ηp2 0,266). Parents’ occupations do not influence santri’s well-being, as the pesantren provides equal facilities and treatment to all santri regardless of their social status. Seventy-five percent of santri at Pesantren X exhibited a moderate level of well-being. The results suggest implementing an orientation period to facilitate santri’s transition from home to pesantren, enhancing their self-adjustment ability and consequently improving their well-being